2018
DOI: 10.1002/jcb.28148
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated radiotherapy might induce epithelial‐mesenchymal transition and radioresistance in a cellular context manner

Abstract: Despite the fact that radiotherapy is a main therapeutic modality in cancer treatment, recent evidence suggests that fractionated radiotherapy (FR) might confer radioresistance through epithelial‐mesenchymal transition (EMT). Nevertheless, the effects of FR on EMT phenotype and the potential link between EMT induction and radioresistance development yet to be clarified. The aim of this study was to assess whether FR could promote EMT, and to elucidate if induction of EMT contributes to the acquisition of radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Although our data show no significant changes in the expression of E-cadherin, it does not necessarily mean that radiation does not promote invasiveness and metastatic potential in cancer cells, due to the fact that the change of E-cadherin gene is not the just activator of cell migration and invasion. Moreover, according to Ikeguch et al, and Akimoto et al, there is a complex process behind the expression of Ecadherin in metastatic foci of colorectal cancer cells, which might lead to E-cadherin overexpression with negative function [17][18][19][20][21][22][23][24][25][26][27]. In addition, according to molecular studies, Wnt/ βcatenin, STAT3 and ZEB1 are reported as the most important signaling pathways associated with E-cadherin expression in colorectal cancer cells [12,28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although our data show no significant changes in the expression of E-cadherin, it does not necessarily mean that radiation does not promote invasiveness and metastatic potential in cancer cells, due to the fact that the change of E-cadherin gene is not the just activator of cell migration and invasion. Moreover, according to Ikeguch et al, and Akimoto et al, there is a complex process behind the expression of Ecadherin in metastatic foci of colorectal cancer cells, which might lead to E-cadherin overexpression with negative function [17][18][19][20][21][22][23][24][25][26][27]. In addition, according to molecular studies, Wnt/ βcatenin, STAT3 and ZEB1 are reported as the most important signaling pathways associated with E-cadherin expression in colorectal cancer cells [12,28].…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is one of the most important modalities for cancer treatment. However, according to recent clinical and experimental studies, ionizing radiation might induce invasion and enhance metastasis potential in cancer cells [3,8,19,20,23,24]. Moreover, recent studies have demonstrated that changes undergoing in cell-cell adhesion and cell-extracellular matrix interaction in post-irradiated tumor cells might cause them to loss their epithelial characters and acquire mesenchymal morphology which lead to enhanced potential for migration, invasion and metastasis [9,18,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiotherapy is an essential modality that can be implemented at various phases in the cancer treatment process; 59 approximately 50% of cancer patients annually receive radiotherapy either alone or in combination with other modalities. 60 Radioresistance in cancer cells causes recurrence of diseases and treatment failure, which is a major clinical obstacle for the treatment by radiotherapy. 61,62 Exosomes modulate the radioresistance of head and neck cancer cells, as indicated by higher overall survival and accelerated DNA repair in cells treated with exosomes isolated from irradiated cells.…”
Section: Radiotherapymentioning
confidence: 99%
“…Radiotherapy is an essential modality that can be implemented at various phases in the cancer treatment process; approximately 50% of cancer patients annually receive radiotherapy either alone or in combination with other modalities . Radioresistance in cancer cells causes recurrence of diseases and treatment failure, which is a major clinical obstacle for the treatment by radiotherapy .…”
Section: Radiotherapymentioning
confidence: 99%